Chrysanthemum (Chrysanthemum morifolium) CmICE2 conferred freezing tolerance in Arabidopsis - Zhang, Zhaohe (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2019 Elsevier Masson SAS. All rights reserved.